Ultra low dose aerosol challenge with Mycobacterium tuberculosis leads to divergent outcomes in rhesus and cynomolgus macaques. (January 2016) - Sharpe, Sally; White, Andrew; Gleeson, Fergus; McIntyre, Anthony; Smyth, Donna; Clark, Simon; Sarfas, Charlotte; Laddy, Dominick; Rayner, Emma; Hall, Graham; Williams, Ann; Dennis, Mike
Summary: Well characterised animal models that can accurately predict efficacy are critical to the development of an improved TB vaccine. The use of high dose challenge for measurement of efficacy in Non-human primate models brings the risk that vaccines with the potential to be efficacious against natural challenge could appear ineffective and thus disregarded. Therefore, there is a need to develop a challenge regimen that is more relevant to natural human infection. This study has established that ultra-low dose infection of macaques via the aerosol route can be reproducibly achieved and provides the first description of the development of TB disease in both rhesus and cynomolgus macaques following exposure to estimated retained doses in the lung of less than 10 CFU of Mycobacterium tuberculosis. CT scanning in vivo and histopathology revealed differences in the progression and burden of disease between the two species. Rhesus macaques exhibited a more progressive disease and cynomolgus macaques showed a reduced disease burden. The ability to deliver reproducible ultra-low dose aerosols to macaques will enable the development of refined models of M. tuberculosis infection for evaluation of the efficacy of novel tuberculosis vaccines that offers increased clinical relevance and improved animal welfare.